Laser eye procedure is safe and effective as an early treatment for glaucoma. (10th July 2019) - Cook, Rob; Thomas, Vaughan; Martin, Rosie
The study: Gazzard G, Konstantakopoulou G, Garway-Heath E, et al. Selective laser trabeculoplasty versus eye drops for first-line treatment of ocular hypertension and glaucoma (LiGHT): a multicentre randomised controlled trial. Lancet 2019; doi:10.1016/S0140-6736(18)32213-X . This project was funded by the NIHR Health Technology Assessment Programme (project number 09/104/40) and was sponsored by the Moorfields Eye Hospital NHS Foundation Trust. To read the full NIHR Signal, go to https://discover.dc.nihr.ac.uk/content/signal-000774/early-glaucoma-laser-eye-treatment-trabeculoplasty